Ensuring the integrity of charitable organisations - Abdul Manaf, Zati Ilham; Ali, Zuraidah (Star Media Group Berhad, 2023)
Malaysians are well known for their generosity when it comes to helping others. During the Covid-19 pandemic, for example, numerous campaigns were organised by groups and individuals alike to raise funds or collect food donations to give to those who were most impacted by the adversity. And Malaysians nationwide responded wholeheartedly. Their generosity is not just extended to their fellow Malaysians but also to people facing crises in other countries, including the Palestinians in Gaza. Our eagerness to help those in need is a testament to our spirit of giving.